State's General Obligations regarding the Prevention and Punishment of Crimes Against Humanity: A Review of Draft ILC Articles - Ashri, Munif (Uti Possidetis: Journal of International Law, 2023)
Crimes against humanity  is one of the most serious international crimes in which its criminalization has taken place since the Charter of Nürnberg International Military Tribunal was signed in 1945. But until now, no specialized international treaty dedicated to regulating many aspects of crime againts humanity. In 2019, the International Law Commission (ILC) concluded a Draft Articles on Prevention and Punishment of Crimes Against Humanity, expected to be a basis for a specialized convention in the future. This paper discusses the State’s general obligations concerning the prevention and punishment of crime againts humanity according to ILC’s Draft Articles. This paper used the juridical-normative research method by combining the conceptual and statute approach. The result of the discussion found that there are three general forms of State obligations, i.e: (1) Obligation not to engage in acts that constitute crime againts humanity; (2) Obligation to prevent; and (3) Obligation to punish.